Energy Efficient Homes: Green Certification Programs - Nicholas W. Taylor; Barbra Larson; Jeffrey Michael (EDIS, 2008)
FCS-3278, a 5-page fact sheet by Nicholas W. Taylor, Barbra Larson, and Jeffrey Michael, reviews several of the more popular certification programs used in Florida. Includes references. One of an Energy Efficient Homes series. Published by the UF Department of Family Youth and Community Sciences, June 2008.